On vernacular forms: tradition and the Masjid in Malaysia and South East Asia - Mohd Nawawi, Norwina; Abdul Majid, Noor Hanita (MPH Group Printing (M) Sdn Bhd, 2016)
This chapter explore the vernacular architecture of the Malays through Masjid built form from the Malay Archipelago as case studies.